Depression, anxiety and stress levels among frontliners of hospital-based (SASMEC) and university campus (IIUM Kuantan) during covid-19 pandemic and its associated factors - Abdullah, Fa’iza; A. Rahman, Nor Azlina; Mohd Basri, M. Arif Mustaqim; Nik Ahmad, Nik Nur Fatnoon; Md Aris, Mohd Aznan; Samsudin, Suhaiza; Ahmad Basri, Nadzirah; Mat Nor, Mohd Basri (2022)
The COVID-19 pandemic or endemic has instigated a substantial physical and psychological burden on the frontliners globally, which lead to harmful consequences on emotional and mental health such as physical and psychiatric disorders, reduction in productivity, loss of commitment and burnout. Hence, assessing their mental health status is essential as an access point in providing appropriate mental health care. This study aimed to measure depression, anxiety, and stress level and their associated factors among the frontliners working at the International Islamic University Malaysia (IIUM) Kuantan Campus and SASMEC-Hospital during the COVID-19 pandemic.